Assessment of antibacterial and antioxidant properties of torch ginger (Etlingera elatior Jack) inflorescence essential oil in starch-based edible film for chicken meat packaging - Marzlan, Anis Asyila (2021)
Essential oils (EOs) are used extensively in wide applications to alternative synthetic compounds. Supercritical carbon dioxide (SC-CO2) extraction is a sustainable green technology and achieves high purity with better retention of aromatic compounds. The application of torch ginger (Etlingera eliator Jack) inflorescence essential oil (TGIEO) in the active packaging system could offer new opportunities to develop a novel food packaging system as functional constituents in order to prolong the shelf-life of food products and ensuring their quality and safety. The poultry processing sector, such as chicken meat, provides a sustainable animal protein source, but it is very perishable and prone to oxidation and microbial growth. Incorporating EOs in active packaging could reduce environmental impacts as reduced chemical waste and offer protection to enhance safety and extend poultry meat's shelf life. Thus, the study' s objectives were to optimize the pressure and temperature of SC-CO2 extraction for TGIEO, evaluate the antioxidant and antibacterial activities of TGIEO incorporation into a starch-based edible film as active packaging, and determine the physicochemical, coliform count, rancidity and sensory analysis of chicken meat packed with TGIEO incorporated into the starch-based edible film during chilled storage. Response surface methodology (RSM) combined with the central composite (CCD) design was employed to optimize the SC-CO2 extraction conditions which the optimized TGIEO was further incorporated into starch-based active packaging by drying the film-forming solution (FFS) via the casting method. The functional properties of this film in food system were observed by packing the chicken meat samples with TGIEO incorporated into the starch-based edible film (TF). The optimized SC-CO2 extraction conditions were pressure 286.4 bar and temperature 57.3°C. The TGIEO incorporated into starch-based edible film showed positive antibacterial activities against six pathogenic bacteria (Bacillus subtilis, Staphylococcus aureus, Listeria monocytogenes, Salmonella Typhi, and Escherichia coli) and showed inhibition zone (6.0 ± 0.01 - 23.0 ± 0.12 mm). The phytochemical activities of this active packaging were DPPH (67.36 ± 2.48%) and ABTS+ (84.78 ± 0.57%), respectively. At the end of the chilled storage period (3°C ± 1), the chicken sample TF showed the lowest coliform count (4.98 ± 0.07 CFU/g) and the lowest TBARS value (0.212 ± 0.31 mg MDA/kg). There is no significant difference (p<0.05) for all the chicken samples for sensory analysis and concluded that the TGIEO does not affect the organoleptic properties. Thus, the optimized SC-CO2 extracted TGIEO incorporated into starch-based edible fihn showed significant antibacterial and antioxidant film properties that potentially extends the quality of chicken meat during the chilled storage period.